Education, Self-Importance, and the Propensity for Political Participation - Caffrey-Maffei, Lucy (Perceptions, 2019)
Past research has largely centered on the link between education and political participation. Although an array of evidence has suggested that there is a positive—if not causal—relationship between the two, some suggest that the relationship is spurious or mediated by other factors. Using data from the General Social Survey (2004-2014), the present study intends to revisit the phenomenon while controlling for self-importance in order to resolve the previous conflicting findings. The bivariate cross-tabulation indicates that educational attainment is a significant determinant of political participation. The trivariate cross-tabulation, furthermore, uncovers that self-importance confounds the relationship between education and political participation, such that the impact of education on political participation is stronger among those who feel less important. To be sure, the higher a person’s educational attainment is, the more likely they are to participate in political processes; and, moreover, this is particularly true of those who have depressed understandings of their importance in the world. These findings suggest that those with low levels of self-importance—likely traditionally marginalized, stereotyped, or stigmatized groups—are least represented by government officials and mandates. This, in turn, creates an American governance that fails to adequately serve and represent the desires and needs of all its people. The study calls on further research to explore the impact of other related variables on the relationship between education and political participation, and to create more appropriate and comprehensive measures of political participation and self-importance.